Empowering Posyandu Cadres through Enhancing Parenting Communication Skills to Strengthen Community-Based Family Education - Inne Pujianti; Catur Wulandari (Jurnal Pengabdian IPTEK, 2026)
This community service program was conducted at Posyandu Teratai, South Tangerang, with the aim of enhancing parenting communication skills among female health cadres. Traditionally, posyandu has focused primarily on maternal and child health services, while its potential as a center for community-based family education has not been optimally utilized. Field observations revealed that many mothers continue to apply authoritarian or permissive communication patterns, which may hinder children’s emotional and social development. The program employed a participatory approach that included socialization activities, interactive training sessions, role-play simulations, group discussions, and continuous mentoring. Evaluation was carried out using pre-test and post-test instruments, observations, and reflective forums. The results of the program indicated an improvement in participants’ understanding and application of democratic and empathetic parenting communication. The cadres demonstrated increased confidence and enhanced ability to establish two-way communication with children, and began to assume roles as change agents within their communities. The novelty of this program lies in its effort to position posyandu cadres not only as health facilitators, but also as community educators in family communication. Overall, the program contributes to strengthening family resilience and expanding the social role of posyandu within the community.